DESA WISATA PENTINGSARI; UPAYA PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN DESA WISATA - Kusumah Admaja, Tyas Kusumah Admaja; Anggraini, Oktiva (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
Efforts to empower people in managing Pentingsari tourism villages are described through aspects of access to natural resources that are managed as tourism objects and local wisdom, human resources that have the potential to become managers and establish cooperation with the tourism agency and the private sector (banking). The aspect of participation has been manifested in community participation in various village tourism activities (reception, attractions, companion activities and others). The Control Aspect has been carried out by the Sleman Regency Tourism Office through mentoring activities such as the Tourism Village festival competition which is held once a year, and the evaluation every two years on all Tourism Villages in Sleman Regency and the establishment of a communication forum between Tourism Villages. The benefit aspect for the community from the tourism village management is in the form of material (wages as a companion to the activity) and non-material benefits in the form of capacity building regarding the management of the tourism village, organizational management, financial management and improvement of group work